Comparing Role Playing Model And Group Guidance To Improve Students’ Entrepreneurship Skills - Shendy wijaya; Muhammad Basri Fanani (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2019)
This study compares the effectiveness of learning model use role playing and group guidance in improving entrepreneurial skills. This study applied true experimental design with postest-only control design model and pretest-postest control group design. The study was conducted on undergraduate students in FPIPS IKIP PGRI Jember as an experimental class with undergraduate students of economic pedagogy in FKIP University Jember as a control class. The finding showed that the role-playing games learning are more effective model instead of group counseling-based learning to improve students’ entrepreneurial skills and spirits. For this findings, it is suggested to the lecturer of this course to not only provides theoretical basis but also required to portray the entrepreneurial spirit.